Academics' use of courseware materials: a survey - Diana Laurillard; Betty Swift; Jonathan Darby (Association for Learning Technology, 1993)
Learning technology has yet to enter the mainstream of higher education. The UFC-funded Teaching and Learning Technology (TLT) programme is attempting to change this by sponsoring projects concerned with courseware production and delivery. These efforts could be thwarted if the Not Invented Here syndrome prevents the use of technology-based teaching and learning materials outside the originating departments. To gain a clearer understanding of why academics have been rejecting much existing courseware, and to establish the extent of the Not Invented Here syndrome, we carried out a survey of 800 academics in eight UK universities. The survey proved to be exceptionally revealing.